THE ROLE OF WOMEN IN ECONOMIC DEVELOPMENT IN MAKASSAR - Nurliana; Usman, Mahyudin; Wijhah; Sulfiana (Islamic Financial And Accounting Review, 2024)
This research aims to find out (1) to what extent is the role of women in economic development in Makassar City? (2) what factors hinder the role of women in economic development in Makassar City? The research method uses field research methods. The data obtained is qualitative in nature and is presented in a descriptive qualitative manner. All data collected, both primary data and secondary data, used as research material are discussed using the above. The results of this research reveal that the role of women in economic development has significant results. The obstacles experienced by women are (1) difficulty managing time, (2) unsupportive work environment, and (3) insufficient income.